Queer communal kinship now! (PUNCTUM BOOKS, 2023)
Queer communal kinship is a long overdue replacement for the naturalized model of the modern western family; a post-capitalist regime of social reproduction, aiming for redistributive justice through the politics of pleasure; a timely proposal for the demise of possessive and accumulative ideology, and the upsurge of a counter-imaginary; a manifesto for the collectivization of reproductive labor; an ethical conceptual framework for a joyful cultural shift: Queer Communal Kinship Now! This manifesto pushes for a radical redefinition of love, intimacy, and care in support of a much needed redistributive justice movement. This project must be accompanied by an exit from heteronormativity as a regime of relational scarcity, as well as from the metaphysics of private property which is at the heart of our economies and by extension of our social ecologies -- at odds with much of life on this planet. Queer Communal Kinship Now! examines the role of western normative family ideals in the mechanisms of the preservation and intensification of this status quo, as well as potential approaches to guide us out of this unsavory situation. Both handbook and personal narrative, Queer Communal Kinship Now! discusses the conceptual leaps required to emancipate ourselves from the conventional western family model, towards different regimes of bonding, care, and attention, to allow us to imagine a different type of social reality driven by queer and feminist ethical concerns. Directed to those interested in building queer families and wondering how not to repeat the mistakes of their parents, Queer Communal Kinship Now! offers radical ways of rethinking being together.